Molecular identification of Klebsiella pneumoniae and expression of immune genes in infected spotted gar Lepisosteus oculatus. Issue 119 (December 2021) - Wu, Yaxin; Yang, Yibin; Dang, Huifeng; Xiao, Hehe; Huang, Wenji; Jia, Zhao; Zhao, Xin; Chen, Kangyong; Ji, Ning; Guo, Jiahong; Qin, Zhiwei; Wang, Junya; et al.
Abstract: Spotted gar ( Lepisosteus oculatus ) is a primitive ray-finned fish which has not undergone the third round whole genome duplication and commonly used as a model to study the evolution of immune genes. In this study, a pathogenic strain of Klebsiella pneumoniae (termed KPY01) was isolated from a diseased spotted gar, based on the Gram-stain and phylogenetic analysis of the 16S rDNA and khe genes. Further, the virulence genes and drug resistance genes were determined and drug sensitivity tests were performed to explore the virulence and drug resistance of the KPY01. Putative biosynthetic gene clusters (BGCs) for the biosynthesis of secondary metabolites were predicted using the anti-SMASH5.0 online genome mining platform. Histopathological analysis revealed that the immune cells were significantly decreased in the white pulp of spleen of fish infected with K. pneumonia and tissue inflammation became apparent. Besides, the expression of cytokines including interleukin ( il ) -8, il-10, il-12a, il-18 and interferon γ ( ifn-γ ) were shown to be modulated in the spleen, gills and kidney. Our work provides useful information for further investigation on the virulence of K. pneumoniae and host immune responses to K. pneumoniae infection in fish. Highlights: A Klebsiella pneumoniae strain was isolated from a diseased spotted gar. Virulence and drug resistance genes were determined. K. pneumoniae consists of biosynthetic gene clusters for discovery of bioactive natural products. K. pneumoniae infection leads to upregulation of proinflammatory cytokines in the kidney and spleen of spotted gar.